Pengaruh Nilai Tukar, Suku Bunga dan Transaksi Digital terhadap Velocity of Money di Indonesia - Anne Fitrianovaline; Stannia Cahaya Suci; Muhammad Nasim Harahap (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effects of the exchange rate (NT), Bank Indonesia policy interest rate (SB), e-money transaction volume (VUE), e-moneytransaction value (NUE), and the number of Electronic Data Capture (EDC) machines on the Velocity of Money in Indonesia during the period of 2021M1–2025M12. The study is motivated by the digital paradox phenomenon, in which the rapid growth of digital payment transactions has not been accompanied by an increase in the Velocity of Money. This research employs a quantitative approach using monthly time-series data obtained from Bank Indonesia and Statistics Indonesia (Badan Pusat Statistik). The analysis is conducted using the Autoregressive Distributed Lag (ARDL) model with two dependent models, namely the M1-based Velocity of Money (VOM1) and the M2-based Velocity of Money (VOM2). The findings indicate that, in the short run, VOM1 is significantly influenced by e-money transaction value (NUE), the number of EDC machines, and the fourth lag of the policy interest rate, while VOM2 is negatively and significantly affected by e-money transaction volume (VUE) and EDC. In the long run, VOM1 is positively and significantly influenced by the policy interest rate, whereas NUE and EDC have significant negative effects. In contrast, VOM2 is negatively and significantly affected by VUE and EDC, while the exchange rate, the policy interest rate, and NUE have no significant effects. This study contributes to the empirical literature by demonstrating that the determinants of the Velocity of Moneydiffer between the M1 and M2 monetary aggregates, thereby providing further evidence of asymmetric responses to macroeconomic factors and the digitalization of payment systems. These findings enrich the monetary economics literature and offer policy implications for Bank Indonesia in formulating more effective monetary and payment system policies.